Mathematical Model of Mercury Capture in the Filter of an Entrained-Flow Reactor System - Tim C. Keener; Kwang-Joong Oh; Sang-Sup Lee (Adsorption Science & Technology)
Results of full-scale tests have shown that mercury capture in a fabric filter is more effective than in an electrostatic precipitator. This is in accordance with our previous experimental results in which significant amounts of oxidized mercury were easily adsorbed in the filter rather than in the entrained-flow reactor portion. In this study, mercury capture in the filter was modelled using a tanks-in-series model. Based on the experimental results of this study, we conclude that the modelling results predicted an effective mercury capture in the filter.